(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This paper discusses how dreams are presented to the Nasa indigenous peoples, seeking to share how certain social and economic dynamics established in the department of Cauca have affected the lives of these populations. In this context, dreams are recognized as zones of resistance that are linked to their own autonomous education systems. The potential of cultivating collective dreams also served as inspiration for the formation of the Study Group on Dreams for Indigenous Peoples in Latin America.